2013
DOI: 10.1007/s12185-013-1356-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor lysis syndrome soon after treatment with hydroxyurea followed by nilotinib in two patients with chronic-phase chronic myelogenous leukemia

Abstract: Nilotinib, a second-generation tyrosine kinase inhibitor with 20- to 30-fold greater potency than imatinib, was developed to overcome imatinib intolerance or resistance. Recently, nilotinib has been approved as a first-line treatment for chronic myelogenous leukemia in the US and Japan. Tumor lysis syndrome (TLS) is an extremely rare adverse event that can occur during treatment with nilotinib, with only a few reported cases to date. Herein, we report two patients who developed TLS soon after the start of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Renal dysfunction has been reported with other TKIs, including imatinib, [6][7][8][9][10]14,[34][35][36] nilotinib, [37][38][39] and dasatinib, 6,9,[11][12][13][14][40][41][42][43] suggesting a possible drug class effect. This is supported by the similar frequency and characteristics of renal decline observed with imatinib and bosutinib treatment in our analyses.…”
Section: Discussionmentioning
confidence: 97%
“…Renal dysfunction has been reported with other TKIs, including imatinib, [6][7][8][9][10]14,[34][35][36] nilotinib, [37][38][39] and dasatinib, 6,9,[11][12][13][14][40][41][42][43] suggesting a possible drug class effect. This is supported by the similar frequency and characteristics of renal decline observed with imatinib and bosutinib treatment in our analyses.…”
Section: Discussionmentioning
confidence: 97%
“…The elderly patient in our center did not experience AKI during the rst year of Imatinib treatment but developed AKI with estimated glomerular ltration rate of 16.14ml/min two years after Nilotinib administration. In 2013, Jin (15) reported Nilotinib-related AKI, which was caused by tumor lysis syndrome (TLS). TLS is characterized by abnormal metabolism and usually occurred at the initial anti-tumor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the elevated TBIL level obviously improved through dose adjustment at the beginning of the TBIL level elevation, which also affected the response of the Bcr-Abl/Abl IS ratio. Hua et al [ 17 ] reported that a 44-year-old man with CML developed metabolic acidosis within 10 hours of nilotinib administration, which rapidly progressed to multiorgan and hepatic failure (bilirubin, 4.4 mg/dL; ALT, 1031 U/L). Furthermore, the autopsy showed massive liver necrosis.…”
Section: Discussionmentioning
confidence: 99%